Multimodalidade em duas traduções para Libras em vídeo do poema "Moça linda bem tratada" de Mário de Andrade - Vital, Dafny Saldanha Hespanhol (TradTerm, 2023)
This paper aims to compare two translations into Brazilian Sign Language (Libras) of Mario de Andrade’s poem Moça linda bem tratada, carried out at the Federal University of Rio de Janeiro (UFRJ). One of the two translations under study, deemed in this paper as multimodal products (Diniz & Carneiro 2021; Baptista 2015: 33), was made in the Project Videoteca Acadêmica em Libras (ViaLibras). This analysis shall use the concept of multimodality and its elements design, production and distribution (Kress e Van Leeuwen 2001; Baptista 2015), and also present and compare some translation choices in each translation, drawing a parallel with the idea of re-creation in translation of creative texts (Campos 1967 [1962]), and writing resources, such as the use of rime and rhythm in sign languages (Klamt 2014). We expect to raise Libras translators’ awareness of the applicability of multimodality aspects.